2013 IEEE International Conference on Solid Dielectrics (ICSD) 2013
DOI: 10.1109/icsd.2013.6619867
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of space charge behavior of oil-cellulose insulation systems by means of the PEA method

Abstract: Despite recent advancements in material technology, oil-cellulose insulation systems in form of so called Transformerboard combined with paper and mineral oil are still one of the backbones of high voltage technology. This insulation system is widely used in the high voltage industry, especially in high voltage transformers for AC and HVDC applications, e.g. converter transformers. The space charge behaviour of Transformerboard has rarely been investigated, causing the presumption oil-cellulose insulation syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Results from Southampton in [14] show that the moisture content, even within 5%, has a great influence on the charge injection, movement and accumulation. The higher the moisture content of the oil-paper sample, the higher the mobility of the charges, and more positive charge injection and negative charge injection were observed.…”
Section: Karamay 25#mentioning
confidence: 99%
See 1 more Smart Citation
“…Results from Southampton in [14] show that the moisture content, even within 5%, has a great influence on the charge injection, movement and accumulation. The higher the moisture content of the oil-paper sample, the higher the mobility of the charges, and more positive charge injection and negative charge injection were observed.…”
Section: Karamay 25#mentioning
confidence: 99%
“…A series of measurements were carried out where an oil-paper insulation system was subjected to different test temperatures (from 15˝C to 60˝C) [11][12][13][14]. The results showed that the temperature had a limited effect on the threshold voltage of the space charge.…”
Section: Test Temperaturementioning
confidence: 99%
“…[6][7][8][9] The PEA method was originally developed to measure space charge distribution in polyethylene, but has since then been applied to a broad variety of substances, such as epoxy resin, 10) polyimide, 11) silicone rubber, 12) and oil paper. [13][14][15][16][17][18][19] With the exception of oil paper, the substances that are used in the PEA method are homogeneous solids unless they are specially treated, for instance by nanoparticles addition. Oil paper is widely used as the main insulation material in convert transformers.…”
Section: Introductionmentioning
confidence: 99%
“…It is a composite dielectric consisting of porous insulation paper that is permeated by insulation oil. Existing research reports on space charge in oil paper do not address electric field distribution, [13][14][15][16][17][18][19] which stands out compared with other studied materials. The PEA method is based on the elastic wave propagation in a solid and on the hypothesis that the contact interface is perfect; 9) however, these prerequisites are occasionally not satisfied in space charge measurements.…”
Section: Introductionmentioning
confidence: 99%